If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -6x + -3 = -40 + 4x + -15 Reorder the terms: 8 + -3 + -6x = -40 + 4x + -15 Combine like terms: 8 + -3 = 5 5 + -6x = -40 + 4x + -15 Reorder the terms: 5 + -6x = -40 + -15 + 4x Combine like terms: -40 + -15 = -55 5 + -6x = -55 + 4x Solving 5 + -6x = -55 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + -6x + -4x = -55 + 4x + -4x Combine like terms: -6x + -4x = -10x 5 + -10x = -55 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -10x = -55 + 0 5 + -10x = -55 Add '-5' to each side of the equation. 5 + -5 + -10x = -55 + -5 Combine like terms: 5 + -5 = 0 0 + -10x = -55 + -5 -10x = -55 + -5 Combine like terms: -55 + -5 = -60 -10x = -60 Divide each side by '-10'. x = 6 Simplifying x = 6
| -3x-12=4x+16 | | -18+4x=-2x | | -8x-9=39 | | -8x-9=29 | | y^2-4x^4=0 | | 6e^4x+13e^2x=28 | | -4y+1=2 | | B/7-11=7 | | 12+13=7x-7 | | -15=c-15 | | 8(-13)-3(-13-5)=4(-13)+4(-13+6) | | 2y-4=3y-9 | | 8-2b=-2/3(12b+6) | | y=+25 | | 13/15(x-3y-5z) | | 2(z-1)/2z-3-3(z+2)/2z-3-z-1/3-2z | | 1.72g-9=0.46 | | x^2-(5-i)x+6=0 | | 28=k+14 | | 2x+9x=-5 | | 5/7d=45 | | 1/8/1/3(2)=x | | 3+8x-6=6x+7 | | C/-10=-5 | | 5a+4b=20 | | 2Xsquared+9X=-5 | | 48-x+22+2-x= | | 4a=0.36 | | −3y+7+1 | | 5x+2x-4=38 | | 2(2x+3)-2=4(x+1) | | -18x+2=3x |